Teacher Skills on Islamic Cultural History Learning Outcomes in Senior High School - Nuraiman, Nuraiman; Nofriani, Desi; Dasrizal, Dasrizal; Mutathahirin, Mutathahirin (Suluah Pasaman, 2024)
The teaching and learning process in many classrooms remains largely teacher-centered, often leading to student passivity and boredom. This can negatively impact learning outcomes, particularly in subjects like Islamic Cultural History, which require active engagement and contextual understanding. To address this issue, teachers need to develop and apply basic teaching skills, including the ability to open and close lessons effectively, ask thought-provoking questions, provide reinforcement, deliver clear explanations, manage the classroom efficiently, and apply varied teaching strategies. This study aims to describe the basic teaching skills demonstrated by teachers in Islamic Cultural History classes, assess student learning outcomes in the subject, and explore the correlation between teachers' basic teaching skills and student learning outcomes in Class X at Madrasah Aliyah Negeri 1 Pasaman. The findings are expected to highlight the importance of teaching competence in improving student performance and creating a more engaging learning environment.